DNA-based detection of Rat in the meatballs product using a real-time polymerase chain reaction method - Etin Diah Permanasari; Hadi Sunaryo; Adia Putra Wirman; Nuriza Rahmadini; Savira Yustinah Aggasy; Nurul Azmah Nikmatullah (Pharmaciana)
The meat-based products are highly susceptible to counterfeiting, primarily due to high consumer demand of meat derivative products, such as meatballs. This demand creates opportunities for food fraud by specific industries, including adulterating meat with non-halal species, such as rats. This research aimed to detect rat meat contamination in meatball samples from the Indonesian local market using Real-time Polymerase Chain Reaction (RT-PCR). The RT-PCR amplification involved an initial denaturation step at 95°C for 3 minutes, followed by denaturation at 95°C for 15 seconds, and annealing/extension at 60°C for 1 minute. The rat-specific probe primer included in the kit produced an increasing curve in the External Positive Control (EPC) with a Ct value of 27.22, and no amplification occurred in the Negative Control (NTC). The analysis of 30 samples from meatball vendors yielded negative results, as there was no increase in the FAM (rat) curve, indicating that none of the meatballs were contaminated with rat DNA.